English translation of harf min in surah yasin: acomparative study of Muhammad Marmaduke Pickthall's and Abdullah Yusuf 'Ali's translation - Lisda Farikhatunnisak (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2013)
har,1/oen, .01